A gestação de alto risco e o medo do colapso: o trabalho psíquico de gerar vida - Gasparin, Gustavo (My University, 2021)
To gestate a baby is a job that involves biological and psychological aspects. In a high-risk pregnancy, the psyche is confronted with the fear of interruption of pregnancy, complications in the baby's development or the possibility of death for both. The aim of this dissertation is to articulate Winnicott's concept of fear of breakdown and the psychism in high-risk pregnant women. For this, fantasies and anxieties in pregnant women facing a highrisk pregnancy from hypertension were identified. Another point was to deepen Winnicott's theoretical concept of fear of breakdown, and associated themes. In addition, few possible interventions in cases of high-risk pregnancy were identified. The present work is a qualitative and exploratory research, conducted by a multiple cases study. Four high-risk pregnant women from the General Hospital of Caxias do Sul, a reference to the SUS, participated in the study. Those who were experiencing hypertension during the gestational period, living their first high-risk pregnancy, were included. A semi-structured interview was carried out and the Drawing-Story procedure with a theme was introduced, in order to deepen the understanding of the psychism aspects presented in this sensitive moment of maintenance of the pregnant woman's life and generation of a new being. The results were analyzed and discussed through content analysis, according to the mixed model, eight categories were proposed: life story elements; violence, abandonment and trauma; mourning; experiences and expectations of pregnancy; high-risk pregnancy; dreams; possible signs of fear of breakdown and, finally, expectations for the future. In the discussion, the concept of fear of breakdown and the experiences of pregnant women at high risk were articulated with relevant and current authors, highlighting Roussillon, integrating the original trauma and the return of the splitted with the understandings of Winnicott. The most primitive faults, from the mother environment, leave marks of something not lived. Pregnancy in the ambience of death threat implies the possibility of returning something that was not integrated. It arises a new possibility of experiencing the traumatic situation, a possible moment of re-signification, or maintaining the symptoms of what is still unnamable. In the end, the psychological work of pregnancy involves regressing, identifying with the baby and the baby she was. In an attempt to experience the unexperienced, they can understand themselves more and live the mourning of elements of their own history, when not lived in their fullness. [resumo fornecido pelo autor]
Gestar é um trabalho que envolve aspectos biológicos e psicológicos. Na condição de uma gestação de alto risco, o psiquismo é posto em prova frente aos receios de interrupção da gravidez, complicações no desenvolvimento do bebê ou possibilidade de óbito de ambos. O objetivo desta dissertação é identificar possíveis articulações entre o conceito de medo do colapso de Winnicott e as vivências da gestante de alto risco. Para isso, identificou-se fantasias e ansiedades nas gestantes diante de uma gestação de alto risco, decorrente de hipertensão. Buscou-se o aprofundamento do conceito teórico de medo do colapso de Winnicott, e temas associados. Além disso, identificou-se algumas formas possíveis de intervenção nos casos de gestação de alto risco. O presente trabalho trata-se de uma pesquisa qualitativa e exploratória, conduzida pelo estudo de casos múltiplos. As participantes deste estudo foram quatro gestantes de alto risco do Hospital Geral de Caxias do Sul, referência ao SUS no atendimento a este público. Foram incluídas aquelas que apresentaram hipertensão arterial durante o período gestacional, vivenciando a primeira gestação de alto risco. Foi realizada uma entrevista semiestruturada e aplicado o procedimento Desenho-Estória com tema, buscando ampliar a compreensão da experiência vivida neste momento delicado de manutenção à vida da gestante e de geração de um novo ser. Os resultados foram analisados e discutidos mediante à análise de conteúdo, seguindo o modelo misto, foram propostas oito categorias: elementos da história de vida; violência, abandono e traumas; lutos; vivências e expectativas da gestação; gestação de alto risco; sonhos; possíveis indícios de medo do colapso e, por fim, expectativas diante do futuro. Na discussão, articulou-se o conceito de medo do colapso e as vivências da gestante em alto risco com autores relevantes e atuais, destacando-se Roussillon, integrando conceitualmente o trauma originário e retorno do clivado com a compreensão de Winnicott. As falhas mais primitivas, do ambiente mãe, deixam marcas de algo não vivido. Gestar na condição de ameaça de morte imprime a possibilidade de retorno de algo que não foi integrado. Surge nova possibilidade de experenciar a situação traumática, momento possível de ressignificação, ou manutenção sintomática daquilo ainda inominável. No final, o trabalho psíquico de gestar, envolve regredir, identificar-se com o seu bebê e o bebê que foi. Na tentativa de vivenciar o não vivido, pode compreender mais a si e viver o luto de elementos da própria história, quando não vividos na sua plenitude. [resumo fornecido pelo autor]
Keywords: Gravidez - Aspectos psicológicos; Gravidez - Complicações e sequelas; Psicanálise; Mãe e lactente; Pregnancy - Psychological aspects; Pregnancy - Complications; Psychoanalysis; Mother and infant